2005
DOI: 10.1128/aac.49.1.161-169.2005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Promoter Region Mutations and mgrA Overexpression on Transcription of norA , Which Encodes a Staphylococcus aureus Multidrug Efflux Transporter

Abstract: NorA is a Staphylococcus aureus multidrug transporter that confers resistance to structurally distinct compounds. The MgrA global regulatory protein is reported to augment norA expression when mgrA is overexpressed from an undefined plasmid-based promoter. Further details about norA regulatory mechanisms are scant. A chromosomal norA::lacZ transcriptional fusion was constructed in different S. aureus strains, and allele replacement was used to define the relevance of promoter region sequences to norA expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
70
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 43 publications
2
70
1
Order By: Relevance
“…MgrA contains a typical HTH DNA-binding motif and is a member of the MarR family of transcriptional regulators. Similar to CmeR, MgrA also functions as both a repressor and an activator for various genes in Staphylococcus (16,27,43). A recent DNA microarray study indicated that MgrA affects the expression of 355 genes in multiple functional categories in S. aureus (26).…”
Section: Discussionmentioning
confidence: 99%
“…MgrA contains a typical HTH DNA-binding motif and is a member of the MarR family of transcriptional regulators. Similar to CmeR, MgrA also functions as both a repressor and an activator for various genes in Staphylococcus (16,27,43). A recent DNA microarray study indicated that MgrA affects the expression of 355 genes in multiple functional categories in S. aureus (26).…”
Section: Discussionmentioning
confidence: 99%
“…MgrA regulates expression of genes encoding other Nor efflux pumps and virulence factors (8,20,(22)(23)(24)(32)(33)(34), but it does not affect regulation of the opp1-norD operon. Our data show that opp1-norD expression was comparable in S. aureus MW2 and MW2 mgrA mutant in both rich medium and under low free iron conditions (data not shown), suggesting that regulation of opp1-norD is independent of MgrA.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to regulating virulence determinants, MgrA represses the expression of several efflux systems (i.e., NorA, NorB, NorC, and Tet38) that confer resistance to multiple antibiotics (111,224,225). MgrA is a member of the MarR family of regulatory proteins and, as such, has a dimerization domain and a conserved helix-turnhelix domain (28).…”
Section: Mgramentioning
confidence: 99%